A sensory-material study of everyday strategies and tactics in the kitchen - Rania Saraswati Wijayakusumah; Rini Suryantini (Department of Architecture Faculty of Engineering Universitas Indonesia, 2022)
This article explores the idea of cooking as an everyday spatial practice which occurs in a sensorial and material way within the kitchen. Rather than focusing on the physical arrangement and the efficient workflow, the kitchen exists as a space of strategy and tactics in cooking. Cooking is a practice that involves material transformation driven by sensorial experience, which further shapes the spatial strategies and tactics performed within a kitchen. This study explores a routine noodle-cooking practice, observing the participant’s sensory experience and material transformation to demonstrate the kitchen as an everyday space of strategies and tactics. The kitchen becomes a spatial arrangement that celebrates the intertwining between the transformation of material with sensory experience. Such intertwine governed operations of cooking strategies and tactics, arranging the timing of movements, altering sequence of activities, and manipulation techniques of material. Such operation arguably insinuates the kitchen as an idea constructed by the intertwined layers of sensory and material transformation, contributing to expanding the idea of the kitchen from an everyday perspective.